The Effectiveness of Fiscal and Monetary Policy to Respond Challenges of Sustainable Venture Business - Gernego, Iuliia; Dyba, Oleksandr; Mykhailo I. Dyba,; Petrenko, Liudmyla (European Journal of Sustainable Development, 2025)
One of the most significant challenges for modern society is balancing its innovative and sustainable development directions. On the one hand, venture businesses play a crucial role in the challenges we face globally and at the national level. On the other hand, the world faces increased capital for sustainable investment. In particular, recent trends prove the increasing need to encourage venture businesses to balance between commercial effect and sustainable practices implementation, responding to various challenges. In particular, recent trends prove that governmental policies play an increasing role in responding to the challenges of sustainable venture business. Therefore, the research problem is disclosing fiscal and monetary policy instruments as a practical possibility to boost sustainable venture business development. The paper aims to provide evidence on specific features of “traditional” and sustainable venture business. The study analyzes the challenges of sustainable venture business development, providing possible strategies to avoid them. The results section presents findings to determine the potential of different fiscal and monetary policy instruments for responding to the challenges of sustainable venture business. Keywords: sustainable development, venture business, sustainable venture capital, fiscal and monetary policy, venture financing.